A cognitive map of sustainable decision-making in entrepreneurship: A configurational approach. Issue 3 (8th May 2018) - Muñoz, Pablo
Abstract : Purpose: Under what conditions do entrepreneurs make the sustainable decisions they need to develop socially and environmentally responsible new businesses? Explanations of sustainable decision-making have involved various cognitive features; however, it is not yet clear how they play a role in empirical terms and, moreover, how they combine to induce business decisions based on social, environmental and economic considerations. The purpose of this paper is to explore how five cognitive factors combine and causally connect to produce sustainable decision-making in entrepreneurship. Design/methodology/approach: This study uses fuzzy-set qualitative comparative analysis to examine the decision-making of 37 sustainable entrepreneurs. It focuses on a substantive conception of entrepreneurial behaviour to uncover the cognitive antecedents underlying entrepreneurial decisions that involve the explicit development and implementation of measures, targets and strategies aimed at improving its impact on people and the environment. Findings: The configurational analysis reveals a typology comprising five combinations of cognitive factors constituting a comprehensive cognitive map of sustainable decision-making in entrepreneurship, namely: purpose-driven, determined; value-based, vacillating; value-based, unintended; single motive, single solution; and purpose-driven, hesitant. Research limitations/implications: This study demonstrates that no single condition is necessary nor sufficient for triggering decision-making involving social and environmental concerns, revealing five mental models leading to sustainable decision-making. In doing so, this paper responds to recent calls that stress the need for studies capable of uncovering the complex constellation of cognitive factors underlying entrepreneurial sustainable behaviour. Theoretical and practical implications are discussed. Originality/value: This paper provides a systematic characterization of the cognitive underpinnings of sustainable decision-making and offers a basis for organizing the study of sustainable outcomes and configurations of cognitive antecedents. It reconciles prior efforts aimed at characterizing sustainability decisions in the context of SMEs and new enterprises, challenging current models based on awareness, experience and ethical normative frameworks.